Pengaruh Internship Program Dan Company Core Values Terhadap Kinerja Karyawan - Nazhari*, Renata Nabilah Luthfi; Winarno, Alex (JURISMA : Jurnal Riset Bisnis & Manajemen, 2023)
This study aims to describe the effects of internship programs and company core values on employee performance. The methods used were descriptive quantitative and causal methods. The samples were collected using non-probability sampling for data saturation and the samples consisted of 50 employees. Path analysis was used to analyze data and processed by using SmartPLS. The study revealed that internship programs have no direct effect on employee performance, whereas if the internship program variable is bridged by the company core values variable, it will have a significant effect on improving employee performance. From these results, the company needs to ensure that all employees and interns understand and implement the company's core values in all their work activities so that they can improve the performance provided. Keywords: Internship Programs; Company Core Values; Employee Performance; Intern’s Quality; Understanding